Low-pressure silica injection for porosity reduction in cementitious materials. (1st March 2017) - Maddalena, Riccardo; Hamilton, Andrea
Graphical abstract: Highlights: A novel non-destructive technique for cement surface treatment has been developed and proven effective under laboratory conditions. Nano-silica and silica fume can successfully penetrate the cement surface within 14 days and create extra C-S-H. Silica injections are carried out at low-pressure, ca. 20 kPa and this is the first demonstration of a simply applied and effective technique. Abstract: The durability of building materials is related to the presence of cracks as they provide a fast pathway for the transport of liquid and gases through the structure. Restoration and preservation of historic buildings are the potential applications of this novel technique which uses nano-silica and silica fume particles for consolidation. The small particle size range and the high reactivity of nanoparticles allow them to interact with calcium sources naturally present in cement and concrete, forming binding and strengthening compounds such as calcium silicate hydrate. Nanoparticles act as a crack-filling agent, reducing the porosity and increasing the durability of existing materials. In this study we describe the injection of nano-silica, under low water pressure, into hydrated cement paste. This novel technique can tailor the mechanical and hydraulic properties of existing building materials using a simple and non-destructive procedure.